Treatment Of Patients with Chronic Atrophic Nazopharengitis (Eurasian Medical Research Periodical, 2024)
Serum iron is transportable and closely interacts with all types of active iron in the body. A total of 218 patients were examined, followed up for periods from 1 to 6 years. The duration and number of courses of iron therapy depends on the initial level of serum iron and its dynamics during treatment. The amount of iron in the blood serum of donors ranges from 74,8 to 119.0 mg in men 11 from 55,7 to 104,3 mg in women. When examining practically healthy people, we received the following results: for men 62±3,8 mcg, women 67±3,9 mg. In the patients with atrophic rhinitis observed by us, the level of non-hemoglobin iron in the blood was significantly lower than normal and averaged 43±2,5 mcg for men, and 38±2,8 mcg for women. Based on our results, we recommend conservative treatment, including iron supplements and antimicrobial agents, for minor and moderate atrophic nazopharengitis, as well as in all elderly people